Stability of differential systems with rational right-hand sides - Khusainov, D. Ya.; Shevelo, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove theorems which establish estimates for the domain of stability of a differential system with rational right-hand side. We also construct estimates of the convergence of solutions of the system.